2012
DOI: 10.1366/11-06496
|View full text |Cite
|
Sign up to set email alerts
|

Far-Ultraviolet Spectroscopy in the Solid and Liquid States: A Review

Abstract: UV region'' is no longer appropriate for the 120-200 nm region because most recent spectrometers used in this region are not evacuated but instead incorporate a nitrogen purge. This review consists of eight parts: (1) introduction to FUV spectroscopy, (2) brief history of FUV spectroscopy, (3) development of new FUV spectrometers, (4) FUV studies of liquid water and aqueous solutions, (5) FUV spectra of organic molecules in the liquid states, (6) band assignments by quantum chemical calculations, (7) potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 88 publications
(311 reference statements)
0
74
0
Order By: Relevance
“…The peak of H 2 O 2 is not shown in the graph because it is outside the wavelength range of the spectrophotometers -it was measured to be at 160 nm. 47,48) In addition, our earlier reports have shown that plasma treatment also changes the O 2 concentration in DI water. 33,34,49) Therefore, in order to curve-fit the changes in O 2 concentration, we obtained the reference spectrum of O 2 in Fig.…”
Section: Rons Uv-vis Spectra Profilesmentioning
confidence: 87%
“…The peak of H 2 O 2 is not shown in the graph because it is outside the wavelength range of the spectrophotometers -it was measured to be at 160 nm. 47,48) In addition, our earlier reports have shown that plasma treatment also changes the O 2 concentration in DI water. 33,34,49) Therefore, in order to curve-fit the changes in O 2 concentration, we obtained the reference spectrum of O 2 in Fig.…”
Section: Rons Uv-vis Spectra Profilesmentioning
confidence: 87%
“…An absorption peak at 209.2 nm was detected for NaNO 2 and 201.4 nm for HNO 3 . A shoulder of a peak was detected for H 2 O 2 because the H 2 O 2 peak is expected to exist at a much shorter wavelength of 160 nm [27,28]. …”
Section: Uv Absorption Profiles Of Reference Solutionsmentioning
confidence: 99%
“…(32) The areas investigated consist mainly of the Cretaceous sedimentary rocks of the Izumi Group, Cretaceous granitoids, Cretaceous felsic volcanoclastic rocks of the Arima-Ikuno Group, sandstone, mudstone, chert, limestone and basalts of the Japanese accretionary complex of the Tamba belt, sandstone, conglomerate, mudstone, and tuffs of the Miocene Kobe Group, and Plicocene to Pleistocene sand, gravel and clays of the Osaka Group. (1) A geological outline map of Hyogo Prefecture and the sampling points are shown in Figure 1. (32) …”
Section: Examples Of Usefulness Of Fuv Spectroscopy In Studies Of Watmentioning
confidence: 99%
“…(1) To overcome the difficulty in liquid-and solid-state FUV spectroscopy, we recently developed two kinds of FUV spectrometers with quite different designs. (31,43) One is a compact FUV spectrometer by which one can measure spectra of liquid samples down to 180 nm with nitrogen gas purge.…”
Section: Developments Of Two Kinds Of New Types Of Fuv Spectrometersmentioning
confidence: 99%
See 1 more Smart Citation